Fibrin Specific Thrombolysis by Two-Chain Urokinase-Type Plasminogen Activator Cleaved after Arginine 156 by Thrombin - Abercrombie, David M; Buchinski, Bruce; Salvato, Kathleen A; Vovis, Gerald F; Stump, David C; Broeze, Robert J (Thrombosis and Haemostasis, 1990)
Scu-PA was cleaved by thrombin after arginine-156 to yield a two-chain molecule with low amidolytic activity and resistance to cleavage by plasmin. 125I-fibrin-labeled clots were dissolved in vitro by thrombin-cut scu-PA, but only at concentrations 10- to 50-fold greater than that needed for scu-PA. Three hours of incubation produced 100, 80, and 31% lysis with 100, 50, and 25 pg/ml thrombin-cut scu-PA. Thrombin-cut scu-PA, scu-PA, and tcu-PA yielded linear dose responses in the rabbit jugular venous thrombosis model. The dose required to reach 40% lysis was 2 mg/kg for scu-PA, 3 mg/kg for tcu-PA, and 4 mg/kg for thrombin-cut scu-PA. No significant consumption of fibrinogen or alpha2-antiplasmin levels was observed with thrombin-cut scu-PA while the level of fibrinogen and alpha2-antiplasmin decreased to about 50 and 40%, respectively, with scu-PA and to less than 10% of baseline with tcu-PA. Thus, while less potent than scu-PA, thrombin-cut scu-PA appears to be a more fibrin-specific thrombolytic agent than scu-PA.